Evaluation of the efficacy and feasibility of concurrent weekly docetaxel-nedaplatin and hypo-fractionated radiotherapy in atypical histologic subtypes of primary and metastatic mediastinal malignancies - Meng, FanJun; Ai, XinLei; Wang, Bin; Zhou, Yin; Li, Su; Wang, DaQuan; Liu, FangJie; Chen, NaiBin; Zhou, Rui; Guo, JinYu; Huang, XiaoYan; Yin, ShaoHan; et al. (Frontiers in Oncology, 2022)
Background: We aimed to evaluate the efficacy and feasibility of concurrent weekly docetaxel-nedaplatin and hypo-fractionated radiotherapy (hypo-RT) in atypical histologic subtypes of primary and metastatic mediastinal malignancies. Methods: Fifty-four patients diagnosed with atypical primary or metastatic mediastinal malignancies were retrospectively reviewed. 30 patients received concurrent weekly docetaxel and nedaplatin and hypo-RT (CChRT group) and 24 patients had hypo-RT alone (hRT group). Overall response rate (ORR), in-field locoregional progression-free survival (LPFS) and toxicities were analyzed. The radiobiological effect was evaluated by the LQRGC/TCP model, incorporating four "R"s of radiobiology, Gompertzian tumor growth and radio-sensitizing effect of chemotherapeutic agent. The biologically effective doses (BEDs) were calculated. Results: The median follow-up time was 29.2 months for all patients. The ORR was 86.7% in CChRT group, compared with 62.5% in hRT group (p=0.033). The 2-year in-field LPFS of CChRT and hRT group was 73.4% and 47.3%, respectively (p=0.003). There was no significant difference of any >=Grade 3 toxicities between the two groups (p=0.754). The mean total dose and mean BED by the LQRGC/TCP model in CChRT group were 58.2Gy and 72.34Gy, versus 52.6Gy and 67.25Gy in hRT group. Conclusions: Concurrent weekly docetaxel-nedaplatin and hypo-RT achieved promising in-field LPFS and tolerable toxicities compared with hypo-RT alone in different histologic subtypes of primary and metastatic mediastinal malignancies.